THE ROLE OF STAKEHOLDERS IN OPTIMIZING RESPONSIVE SERVICES THROUGH COOPERATION WITH GUIDANCE AND COUNSELING TEACHERS - Habsy, Bakhrudin All; Mustikaningtyas, Rania Putri; Adelia, Fyrza Mariska; Sriandi, Adelia Kusuma (PT Altin Riset Publishing, 2024)
The guidance and counseling program is a design carried out over some time, it is divided into annual programs and semester programs. In this program, there is one service called responsive service, this service must be provided immediately to students to avoid any difficulties in achieving their developmental tasks. The study is based on the limited number of stakeholders in schools who rarely play an active role in performing the programs, which causes the service implementation not to work effectively, including the implementation of responsive services to students. This study aims to determine the role of each stakeholder at the school in optimizing responsive services through collaboration with counseling teachers. This research uses a qualitative method with library research which is used for collecting the data and information through a wide range of literature related to the research. The results of the research are (1) the Definition, objectives, and principles of guidance and counseling; (2) the Definition and objectives of the guidance and counseling program; (3) the Definition, objectives, focus, and responsive service strategy; (4) The role of stakeholders in optimizing responsive services through collaboration with guidance and counseling teachers.